Prevalence of changes in maxillary sinus through digital panoramic radiographs of the Tiradentes University - Silva, Ingrid de Melo (2022)
The maxillary sinuses, an anatomical structure viewed radiographically by a wide radiolucent area in the posterior region of the maxilla and are the largest of the paranasal cavities and can be located on digital panoramic radiographs. In this area, extensions, intrasinusal septum and some pathological changes can be found. This research aims to investigate and determine the prevalence of the main types of anatomical and pathological changes in maxillary sinuses with their exact locations through digital panoramic radiographs from the image bank of the Radiology Clinic of the Tiradentes University (UNIT). The sample consisted of 878 exams, totaling 1756 maxillary sinuses. To assess the association between variables, the non-parametric Chi-square association test was used, with a level of statistical significance at p <0.05. To verify the degree of agreement between the examiners, the Kappa statistical test was used (p <0.001). The data obtained showed that there was a predominante of females (66.2%). A greater number of changes was observed among individuals aged 46 to 55 years (84.78%). Regarding anatomical changes, the intrasinusal septum (69.2%) were more frequent and, as pathological changes, the mucus retention cyst (1.17%). There was a statistical difference between the presence of sinus changes in relation to the age group (p <0.0001). There was a higher prevalence of sinus alterations in women, being statistically significant (<0.0001). This study contributed to the knowledge about the anatomical structure of the studied population, where digital panoramic radiography is an important tool for the diagnosis of changes in the maxillomandibular region.